Extended holiday in Hurghada: Russian women and 'urfi marriage as an 'alternative circuit of survival' - Walby, Joanne (AUC Knowledge Fountain, 2009)
“The effort to identify the enemy as singular in form is a reverse-discourse that uncritically mimics the strategy of the oppressor instead of offering a different set of terms” (Judith Butler, 1990: 18) Since the disintegration of the former Soviet Union, the ―trope of the trafficked Russian1 woman‖ has shaped the fears and perceptions of Russian women moving abroad for work. This discourse reifies fears of exploitation and victimhood but overlooks women‘s ability to rationally consider the risks and benefits of international migration for economic and social reasons. In Egypt, some negative stereotypes have been associated with the Russian population living in Hurghada, a tourist town a 395 km south of Cairo along the Red Sea coast that has sprung up in the past 15 years as Egypt developed its tourism industry. Before coming to Hurghada I didn‘t have a sense of the size of the local Russian population but I had read that it was a transit point for women being trafficking into Israel‘s sex industry.2 Instead I found Russian women making use of their relative mobility and economic privilege as ―white‖ tourists and then later as foreign residents in Egypt‘s fastest-growing tourist town. 3 One aim of this paper is to challenge the trope of the Russian trafficked women and explore the desires,challenges and motivations behind this significant wave of immigration that is turning Egypt‘s Red Sea coast into a multi-cultural community and site of spectacular growth in the tourism and real estate markets.